Can Board of Directors Diversity and Monitoring Intensity Improve Bank Profitability? - Septian Yudha Kusuma; Sudarman Sudarman; Vita Arumsari (Faculty of Economics and Business Universitas Jenderal Soedirman, 2021)
The purpose of this study to analyze the effect of board of directors diversity and monitoring intensity to profitability. Board of directors diversity measured by a composite index of gender, age, education, citizenship, and independence of the board of directors. Meanwhile, monitoring intensity measured by the composition of audit quality, number of meetings, and the number of committee. The objects are banks listed in the Indonesia Stock Exchange period of 2015-2017 with a panel data regression. Selected samples was 40 banks and 120 observation. The results showed that board of directors diversity had a significant negative on profitability, this result provoke a gap to the previous research. While monitoring intensity is positive significant to profitability. Some practical and implications will be discussed in this study.